The relationship between the use of code switching and e-Learning readiness among english language teachers in Sabah: a proposal / Noor Azaliya Jumal, Asmaa AlSaqqaf and Nik Zaitun Nik Mohamed - Jumal, Noor Azaliya; AlSaqqaf, Asmaa; Nik Mohamed, Nik Zaitun (Akademi Pengajian Bahasa, 2021)
Code switching (CS) is a phenomenon that has been reported to take place in foreign language (FL)/second language (SL) classes as a teaching and learning strategy. While some theoretical views believe that CS facilitates the language teaching and learning process, opposite opinions argue that CS is among the reasons responsible for low language proficiency among FL/SL learners. Reviewing relevant literature reveals that the sudden shift in education from physical to virtual classrooms caused by the COVID-19 pandemic has affected the ways and strategies that teachers utilize in language teaching. Very little is known about the relationship between CS and eLearning readiness among language teachers. This paper attempts to investigate whether there is a relationship between these two variables within the context of ESL teaching in Sabah. The study adopts a quantitative approach where a cross-sectional survey is going to be utilized as the research design. A simple random sampling technique will be employed to distribute a questionnaire to the English teachers in Sabah. Additionally, teachers’ perceptions about the use of CS during online classes are going to be explored. It is hoped that this study will provide some insights in relation to the use of CS particularly within the virtual learning contexts.